Stress relaxation due to ultrasonic impact treatment on multi-pass welds. (August 2014) - Gao, H.; Dutta, R. K.; Huizenga, R. M.; Amirthalingam, M.; Hermans, M. J. M.; Buslaps, T.; Richardson, I. M.
Abstract : Ultrasonic impact treatment (UIT) is a relatively novel technique applied to the toe of welded joints to improve the fatigue life by changing the weld geometry and the residual stress state. In this study, the stress relaxation due to ultrasonic impact treatment is investigated on a six pass welded high strength quenched and tempered steel section. Stress measurements in two orthogonal directions were conducted by energy dispersive synchrotron X-ray diffraction. Results show that the application of only ultrasound to a welded component re-distributes the residual stresses more uniformly, while mechanical impacts in combination with ultrasound is an effective way to release the residual stresses. After welding, diffraction peak broadening due to the lattice distortion, characterised by the full width at half maximum (FWHM), is observed in the region of the weld toes. Ultrasonic impact treatment reduces the FWHM at these locations.